The Growth of Freshwater Lobster (Cherax quadricarinatus) in an Aquaponic System with Water Spinach (Ipomoea aquatica) - Yufendira Dharmasanti; Dudi Lesmana; Wiyoto (Universitas Djuanda, 2026)
Abstract This study aimed to evaluate the growth and survival of freshwater lobster (Cherax quadricarinatus) in an aquaponic system integrated with water spinach (Ipomoea aquatica) based on phytoremediation technology. Focused on three treatments: CT (control without water spinach), WS5 (5 water spinach plants), and WS10 (10 water spinach plants). WS5 treatment provided the highest lobster survival rate at 95.8%, compared to the control and WS10 treatments, which were lower. The absolute growth in carapace length, weight, and specific growth rate of the lobster was also better in WS5 compared to the control and WS10. Statistically significant differences (p<0.05) were found in total absolute length growth and daily total length specific growth rate, with WS5 as the most effective treatment. Water quality measurements during the study showed that temperatures across all treatments were within the optimal range for freshwater lobster and water spinach cultivation, between 24.15–28°C. pH values and dissolved oxygen (DO) levels also remained within safe limits. The pH range in the CT and WS5 treatments was relatively wide, indicating active biological processes in the system. Overall, integrating five water spinach plants in the aquaponic system was proven to be the most effective in improving lobster growth performance and maintaining the quality of the cultivation environment. Additionally, the system demonstrated phytoremediation efficiency of water spinach biomass without the need for additional nutrient inputs. This study recommends the use of WS5 as the optimal model for the development of freshwater lobster aquaponics in the future.